PERAN ORANGTUA DALAM MENGENALKAN BAHASA ARAB PADA ANAK USIA DINI DI ERA DIGITAL - Nur, Samsiah; Ritonga, Nur'ainun (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to familiarize the Arabic language to children since early childhood. It is commenced from the family cycle due to Arabic language learning is not only charged to teachers at school but so are parents who also have the same responsibility on it at home. This study applied the qualitative method by qualitative descriptive approach. Data collection was obtained from observation, invented documents, journals, and the researcher’s experience. The results revealed that the role of parents in familiarizing the Arabic language at early age children is realized in three ways, they are; (1) Parenting by direct involvement in Arabic familiarizing from an early age, (2) Utilizing attractive and fun methods in Arabic learning, (3) Effective and proportional use on digital media to ease the learning process on the Arabic language. This study hopefully can help parents at home and teachers at early childhood schools to teach the Arabic language to early-age children.